Long-Term Effectiveness of a Brief Restorative Justice Intervention - Kennedy, Joseph L. D. (International journal of offender therapy and comparative criminology, 2019)
This research investigated the effectiveness of a brief Restorative Justice Intervention. Probationers who attended a Restorative Justice Intervention (n = 383) were compared with probationers receiving treatment as usual (n = 130) over a 2- to 6-year follow-up period. The proportion of individuals who recidivated in the control condition (n = 89, 68.46%) were higher compared with those who recidivated in the intervention condition (n = 127, 33.16%; z = 7.04, p < .001). In addition, among those who recidivated, those in the intervention condition did so less frequently. Qualitative analyses from a postintervention course evaluation given only to the intervention condition showed that 50% of probationers acknowledged an empathic understanding associated with participation. This brief intervention has a positive multilevel impact on restorative justice. Implications of these effects are discussed.